Design & development of compact uniplanar semi-hexagonal ACS fed multi-band antenna for portable system application - Kumar A.; Naidu P.V.; Kumar V.; Ramasamy A.K. (Electromagnetics Academy, 2023)
Antenna feeders; Antenna grounds; Mobile antennas; Slot antennas; Antenna substrates; Coplanar lines; Dual band antennas; Frequency ranges; Measured results; Multiband antennas; Portable system; Rectangular shapes; Microwave antennas